Educational Resource Management and Academic Quality Improvement in Higher Education Institutions - Sembiring, Hendri; Pardede, Mazmur; Ambarita, Indah; Rumahorbo, Yustina Evelina Derita; Irma, Ade; Sartika, Ika (Indonesian Educational Administration and Leadership Journal (IDEAL), 2026)
Educational resource management has become a strategic factor in improving the academic quality and institutional performance of higher education institutions. However, many institutions continue to encounter challenges in optimizing human resources, facilities, financial management, and academic administration to support sustainable quality improvement. This study aims to examine the influence of educational resource management on the academic quality of higher education institutions. A quantitative research design was employed using a survey method. Data were collected through questionnaires, observations, and documentation involving 150 respondents consisting of lecturers, administrative staff, and students from a higher education institution in North Sumatra, Indonesia. The collected data were analyzed using descriptive statistics and inferential analysis, including validity and reliability tests, normality testing, and simple linear regression analysis. The findings reveal that educational resource management has a positive and statistically significant effect on academic quality (β = 0.694, p < 0.001), explaining 44.4% of the variance in academic quality (R² = 0.444). Effective management of human resources, educational facilities, academic administration, and information technology contributes to improving teaching and learning quality, academic services, graduate competencies, and institutional competitiveness. These findings emphasize that systematic planning, efficient resource allocation, continuous evaluation, and the integration of quality assurance practices are essential for strengthening academic performance in higher education institutions. The study provides empirical evidence for institutional leaders and policymakers in developing effective educational resource management strategies to achieve sustainable academic quality improvement and meet national and international higher education quality standards. This study conducted in a single higher education institution in North Sumatra, Indonesia; therefore, the findings should be interpreted within this institutional context. Future studies involving multiple universities and broader institutional settings are recommended to improve the generalizability og the findings.